Engineering hydrophobin DewA to generate surfaces that enhance adhesion of human but not bacterial cells - Boeuf, Stephane; Seebach, Elisabeth; Gotterbarm, Tobias; Richter, Wiltrud (Acta biomaterialia, 2012)
Hydrophobins are fungal proteins with the ability to form immunologically inert membranes of high stability, properties that makes them attractive candidates for orthopaedic implant coatings. Cell adhesion on the surface of such implants is necessary for better integration with the neighbouring tissue; however, hydrophobin surfaces do not mediate cell adhesion. The aim of this project was therefore to investigate whether the class I hydrophobin DewA from Aspergillus nidulans can be functionalized for use on orthopaedic implant surfaces. DewA variants bearing either one RGD sequence or the laminin globular domain LG3 binding motif were engineered. The surfaces of both variants showed significantly increased adhesion of mesenchymal stem cells (MSCs), osteoblasts, fibroblasts and chondrocytes; in contrast, the insertion of binding motifs RGD and LG3 in DewA did not increase Staphylococcus aureus adhesion to the hydrophobin surfaces. Proliferation of MSCs and their osteogenic, chondrogenic and adipogenic differentiation potential were not affected on these surfaces. The engineered surfaces therefore enhanced MSC adhesion without interfering with their functionality or leading to increased risk of bacterial infection.
Available online 1 December 2011
Gesehen am 09.10.2018